Socio-Economic Impact of Government Digitization Programs: A Citizen's Perspective - Olyvia Rosalia; Firayani; Zulham Zulham (PT. Anagata Sembagi Education, 2025)
This study aims to explore the socio-economic impact of digitalization programs implemented by the government, focusing on citizens' perspectives. The research examines the extent to which the digitalization of public services such as e-ID (e-KTP), e-tax, and e-health has improved efficiency, transparency, and accessibility. The method used is a survey involving respondents from various regions, combining quantitative and qualitative analysis to explore public perceptions, adoption, and challenges. The findings show that although digitalization offers convenience for the majority of citizens, there remains a gap in access, especially among those with low digital literacy and residents in remote areas. Moreover, concerns about data privacy and security persist, particularly among vulnerable populations who lack adequate understanding of their rights and protections in the digital sphere. Respondents also expressed differing levels of satisfaction depending on their previous exposure to technology and the quality of local infrastructure. While urban populations generally report smoother adoption and more positive experiences, rural communities often face difficulties due to unstable internet connections and limited assistance in using digital platforms. This disparity underscores the need for targeted interventions, such as community-based training programs and the development of offline-compatible systems. Overall, this study provides evidence that while digitalization holds significant promise for enhancing public service delivery, its success hinges on the government's ability to ensure equitable access, foster public trust, and build digital capacity across all demographics.